Sediments Quality based on Geo-Accumulation Index in Heavy Metals (Pb, Cu, and Cd) of Cengkok Coastal Waters, Banten Bay - Wardani, N. K.; Prartono, T.; Sulistiono, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This area, which is located near the Banten Bay, is quite active with anthropogenic activities such as industry, fisheries, settlements, and shipyards that have the potential to pollute the environment with heavy metals. This study aims to determine the chemical environmental conditions of the waters and the concentration of heavy metals in the sediments of Banten Bay. Sediment samples were taken at five stations consisting of river and bay sections in April, May, July, August, and September 2019. Heavy metal content in sediments was analyzed according to APHA 2012 using hydrochloric acid and nitric acid destruction methods. The results of heavy metal concentrations in sediments were compared with ANZECC 2000 regulations and sediment quality was determined using the Geo-accumulation Index. The sediment at the observation site is dominated by the silt fraction. The concentration of heavy metals in this study was obtained in the form of lead (Pb) ranging from <0.05 to 6.408 mg / Kg, copper (Cu) ranging from 0.059 to 8.791 mg / Kg, and cadmium (Cd) ranging from 0.042 to 0.605 mg / K. While based on The level of heavy metal contamination in sediments using the Geo-accumulation index (I Geo), the value of all metal types in each month has a value <0.000 at all observation stations. Thus it is concluded that the concentration of heavy metals in the sediment is lower than the threshold determined during the observation. So that the metal concentration weight in the sediment has no significant effect on the environment.